Developing a future concept for an online clothing configurator: An evolution of Ridestore’s style creator, 2020 - Mattsson, Alexander; Ohlslöf, Anton (My University, 2020)
The aim of this project was to investigate how Ridestore’s stylecreator could evolve with UX design, an ease of use perspective, in preparation for when they can display fully 3D rendered clothing instead of photographs. The goal was to propose a digital prototype with proof of concepts through visual examples that Ridestore could implement in their online configurator/style creator to show how different sized clothing could fit on different sized bodies with an increased website usability. The project started off by analyzing Ridestore’s current style configurator to understand its strengths and weaknesses in order to design: tasks performed by test participants, questions for follow up semi-structured interviews, and questions to be asked to focus groups. The data from these user tests was used to define functions, requirements and wishes for the end product. All of this resulted in a digital prototype that was created using Figma, an online prototyping tool. Evaluation of the different components in the prototype was conducted through a methodical triangulation between the requirements, data from the user studies and theoretical background on UX design. In the end, it was possible to conclude that the digital prototype is an improvement of Ridestore’s current configurator, as it hypothetically solves all of the requirements and the most important wishes. It is however not clear that it will work perfectly in the end due to the lack of user tests done on the prototype.
Keywords: online, clothing, configurator, style, combinations; Ridestore, usability